Your number one source for unlimited joy, good health and prosperity : providing effective solutions for all your problems - Gaspard, Gillian (Publishingbooks.biz, 2015)
Offers advice on living a happy and healthy life. Provides cooking tips, information on global warming and climate change and tips on how to get rid of the Ebola virus.